2019
DOI: 10.3389/fneur.2019.00504
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Class and Outcome in Post-stroke Infections: An Individual Participant Data Pooled Analysis of VISTA-Acute

Abstract: Introduction: Antibiotics used to treat post-stroke infections have differing antimicrobial and anti-inflammatory effects. Our aim was to investigate whether antibiotic class was associated with outcome after post-stroke infection. Methods: We analyzed pooled individual participant data from the Virtual International Stroke Trials Archive (VISTA)-Acute. Patients with ischemic stroke and with an infection treated with systemic antibiotic therapy during the first 2 weeks after … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In fact, antibiotics treatments have been given to the cases with ischemic stroke for post-stroke infections. A total of three meta-analyses have shown that preventive antibiotic treatment after stroke onset can reduce the infections of post-stroke cases significantly, including the urinary tract infections [ 35 ] and pneumonia [ 36 ]. Nonetheless, none of these studies reported that the use of antibiotics reduces post-stroke functional outcome of the cases [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, antibiotics treatments have been given to the cases with ischemic stroke for post-stroke infections. A total of three meta-analyses have shown that preventive antibiotic treatment after stroke onset can reduce the infections of post-stroke cases significantly, including the urinary tract infections [ 35 ] and pneumonia [ 36 ]. Nonetheless, none of these studies reported that the use of antibiotics reduces post-stroke functional outcome of the cases [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, assessment of safety outcomes was limited to body temperature, body weight and survival: none of these parameters was affected by treatment with azithromycin. Moreover, in a recent retrospective trial, Smith et al (2019) analyzed data from 2708 patients with ischemic stroke and with an infection, treated with systemic antibiotic therapy, grouped into eight different classes, during the first 2 weeks after stroke onset. The results of this study showed that treatment with macrolides was independently associated with a favorable clinical outcome in any infection or pneumonia complicating stroke (Smith et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent retrospective trial, Smith et al (2019) analyzed data from 2708 patients with ischemic stroke and with an infection, treated with systemic antibiotic therapy, grouped into eight different classes, during the first 2 weeks after stroke onset. The results of this study showed that treatment with macrolides was independently associated with a favorable clinical outcome in any infection or pneumonia complicating stroke (Smith et al, 2019). This was ascribed to the favorable immune-modulatory effects and, eventually, to the neuroprotective properties that macrolides display in preclinical stroke settings.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic descriptions of drug effects will not be discussed either. Comprehensive reviews have aggregated a plethora of data describing the phenotypes of action of polyfunctional antibiotics [36][37][38][39][40][41][42]. The reader is kindly referred to these summaries for further information.…”
Section: Introductionmentioning
confidence: 99%